Engaging small and medium enterprises in production networks: Firm-level analysis of five ASEAN economies - Ganeshan Wignaraja (Asian Development Bank Institute (ADBI), 2012)
The Association of Southeast Asian Nations (ASEAN) small and medium enterprises (SMEs) are under scrutiny for their engagement in production networks following recent emphasis on increasing intra-regional trade, rebalancing, and inclusive growth in Asia. Using a data set covering 5,900 firms in five ASEAN economies at different stages of development, this paper analyses the participation of SMEs in production networks, determinants, and policy implications. It finds that although large firms dominate production network engagement in ASEAN economies, there are signs that SMEs have modestly increased their participation since the late-1990s. This is linked to firm-specific factors (e.g., firm size, foreign ownership, skills, technological capabilities, and access to credit) as well as a supportive business environment. Tackling residual supply-side and policy constraints can further the participation of ASEAN SMEs in production networks.
Keywords: F10; F23; O14; 330; small and medium enterprises; production networks; asean; intra-regional trade; KMU; Markteintritt; Internationale Arbeitsteilung; Regionale Wirtschaftsintegration; ASEAN-Staaten